Genome Sequence of Desulfurella amilsii Strain TR1 and Comparative Genomics of Desulfurellaceae Family - Florentino, Anna P.; Stams, Alfons J. M.; Sánchez-Andrea, Irene (Frontiers in Microbiology, 2017)
The acidotolerant sulfur reducer Desulfurella amilsii was isolated from sediments of Tinto river, an extremely acidic environment. Its ability to grow in a broad range of pH and to tolerate certain heavy metals offers potential for metal recovery processes. Here we report its high-quality draft genome sequence and compare it to the available genome sequences of other members of Desulfurellaceae family: D. acetivorans, D. multipotens, Hippea maritima, H. alviniae, H. medeae and H. jasoniae. For most species, pairwise comparisons for average nucleotide identity (ANI) and in silico DNA-DNA hybridization (DDH) revealed ANI values from 67.5 to 80% and DDH values from 12.9 to 24.2%. D. acetivorans and D. multipotens, however, surpassed the estimated thresholds of species definition for both DDH (98.6%) and ANI (88.1%). Therefore, they should be merged to a single species. Comparative analysis of Desulfurellaceae genomes revealed different gene content for sulfur respiration between Desulfurella and Hippea species. Sulfur reductase is only encoded in D. amilsii, in which it is suggested to play a role in sulfur respiration, especially at low pH. Polysulfide reductase is only encoded in Hippea species; it is likely that this genus uses polysulfide as electron acceptor. Genes encoding thiosulfate reductase are present in all the genomes, but dissimilatory sulfite reductase is only present in Desulfurella species. Thus, thiosulfate respiration via sulfite is only likely in this genus. Although sulfur disproportionation occurs in Desulfurella species, the molecular mechanism behind this process is not yet understood, hampering a genome prediction. The metabolism of acetate in Desulfurella species can occur via the acetyl-CoA synthetase or via acetate kinase in combination with phosphate acetyltransferase, while in Hippea species, it might occur via the acetate kinase. Large differences in gene sets involved in resistance to acidic conditions were not detected among the genomes. Therefore, the regulation of those genes, or a mechanism not yet known, might be responsible for the unique ability of D. amilsii. This is the first report on comparative genomics of sulfur-reducing bacteria, which is valuable to give insight into this poorly understood metabolism, but of great potential for biotechnological purposes and of environmental significance.